Developing a digital flipbook to improve science learning outcomes for grade IV SDN 026560 Binjai - Wina Mariana Parinduri; Jeena Ann John; Titin Rahmayanti Rambe; Renni Ramadhani Lubis (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
This study aims to develop and implement a digital flipbook to improve the learning outcomes of IPAS grade IV elementary school students. The research was conducted on grade IV students at SDN 026560 Binjai on the material of the form of substances and their changes. This research is a Research and Development (R&D) study with a 4-D development model: Define, Design, Develop, and Disseminate. The research subjects were fourth-grade students who studied in the odd semester of 2024/2025. The process of developing digital flipbooks to improve the learning outcomes of grade IV students consists of 3 stages of development: the defining stage, the design stage, and the development stage. Based on these stages, the validity of the digital flipbook developed by the researcher was obtained, with the research results from the validity test of media experts in the 93.3% convenient category, material experts of 92.9% in the convenient category, linguists in the 76% valid category, and linguists of 88% in the convenient category. The overall average value of the validity of digital flipbooks is 87.3% with a convenient category, which means that digital flipbooks are suitable to use.